PRELIMINARY OBSERVATIONS ON PADDY-CUM-FISH CULTURE AT HEBBAL - Muddanna, V; Halappa, G; Rajagopal, K V (Indian Journal of Fisheries, 2011)
The preliminary results of paddy-cum-flsh culture experiments at Hebbal withS.317 variety of paddy and the carp, Cyprinus carpio are given in the paper. The productionoffish per hectare based on 71 days of observation ranged from 17.5 kg to152.5 kg and the survival rate varied from 15 to 60%. There is a good scope for improvingpaddy-cum-fish culture practices inspite of some impediments.